Creating organizational and technological automatized control system of water supply of a large city - Дядюн, Сергей Васильевич; Писаревский, Илья Матвеевич; Штельма, Ольга Николаевна (Technology audit and production reserves, 2015)
One of the main problems in the municipal economy is the problem of improving the quality and efficiency of water supply systems. In the very large water systems hidden reserves, the use of which allows to achieve significant savings of unproductive material and energy costs, and improve the provision of the population and industry with water. In this article the structure of the system of water supply control in a big city is presented. These studies are aimed to the full, timely and uninterrupted supply of all consumers of water supply systems of cities in the desired quantity of water specified quality. The structure scheme of a city water supply system which represents the interconnection between subsystems and their functions is worked out. The main problems of automatized system of technological processes control of water supply system while designing are discussed. The analysis of the work of automated process control systems for urban water supply, draws attention to the main difficulties and problems in their construction. Working in a number of cities in the country and the UIC automated process control system for water supply are purely informational. You must be connected to the system of collecting information for a larger number of measured pressure points of the network, and operating an automated process control system of water supply and putting on optimal control. The implementation of organizational and technological automated control system of water supply of large cities, in practice, can significantly improve the quality and efficiency of the water supply, make better use of their internal resources by reducing wastage of water, reducing energy costs, reducing the number of accidents on the network.